Job Strain and the Risk of Stroke. Issue 2 (February 2015) - Fransson, Eleonor I.; Nyberg, Solja T.; Heikkilä, Katriina; Alfredsson, Lars; Bjorner, Jakob B.; Borritz, Marianne; Burr, Hermann; Dragano, Nico; A. Geuskens, Goedele; Goldberg, Marcel; Hamer, Mark; Hooftman, Wendela E.; et al.
<x xml:space="preserve">Abstract</x> Background and Purpose— Psychosocial stress at work has been proposed to be a risk factor for cardiovascular disease. However, its role as a risk factor for stroke is uncertain. Methods— We conducted an individual-participant-data meta-analysis of 196 380 males and females from 14 European cohort studies to investigate the association between job strain, a measure of work-related stress, and incident stroke. Results— In 1.8 million person-years at risk (mean follow-up 9.2 years), 2023 first-time stroke events were recorded. The age- and sex-adjusted hazard ratio for job strain relative to no job strain was 1.24 (95% confidence interval, 1.05;1.47) for ischemic stroke, 1.01 (95% confidence interval, 0.75;1.36) for hemorrhagic stroke, and 1.09 (95% confidence interval, 0.94;1.26) for overall stroke. The association with ischemic stroke was robust to further adjustment for socioeconomic status. Conclusion— Job strain may be associated with an increased risk of ischemic stroke, but further research is needed to determine whether interventions targeting job strain would reduce stroke risk beyond existing preventive strategies.